PURIFICATION AND CHARACTERIZATION OF LIPASE FROM EXTREME HALOPHILES ISOLATED FROM LITTLE RANN OF KUTCH, GUJARAT, INDIA: Life Science-Microbiology - KHUNT, MRUGESH; PANDHI, NEEPA (International Journal of Life Science and Pharma Research, 2012)
Isolation of 30 extreme Halophiles was performed on the medium containing 35% NaCl (w/v) after enrichment in liquid media, designated as Ku-1 to Ku-30. Ku-10, Ku-19 and Ku-20 were selected as best lipase producer from solid media on the basis of zone ratio and were grown in liquid medium containing tributyrin as sole source of carbon. Lipase was partially purified by ammonium sulfate fractionation and highest lipase activity was obtained in 60% saturation fraction. Extracellular lipases from Ku-19 and Ku-20 were active maximally at pH 6 -8 and 40˚C. Lipase from Ku-10 shows greater degree of temperature tolerance and shows highest activity at 60˚C. Additionally, lipases from Ku-19 and Ku-20 denatured in presence of 8 M urea for 2 hours, while lipase from Ku-10 can able to tolerate its effect for 24 hours and retain little activity. Chemicals other than NaCl decrease enzyme activity and chemicals like EDTA and SDS affects activity drastically. After UV mutagenesis, no increase in lipase yield was observed among three halophiles.